2015
DOI: 10.1039/c5nr05341b
|View full text |Cite
|
Sign up to set email alerts
|

Raman fingerprinting of single dielectric nanoparticles in plasmonic nanopores

Abstract: Plasmonic nano-apertures are commonly used for the detection of small particles such as nanoparticles and proteins by exploiting electrical and optical techniques. Plasmonic nanopores are metallic nano-apertures sitting on a thin membrane with a tiny hole. It has been shown that plasmonic nanopores with a given geometry identify internal molecules using Surface Enhanced Raman Spectroscopy (SERS). However, label-free identification of a single dielectric nanoparticle requires a highly localized field comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
(153 reference statements)
0
31
0
Order By: Relevance
“…[ 29,128–131 ] To meet this demand, nano‐aperture POTs have been combined with Raman spectroscopy. [ 132,133 ] Kerman et al experimentally demonstrated the detection and identification of single dielectric nanoparticles trapped in plasmonic nanopores. Raman tweezers comprised of gold coated plasmonic nanopores with intensely confined local fields are capable of trapping and identifying a 20 nm polystyrene nanoparticles with a single SERS peak at 785 cm −1 ( Figure a).…”
Section: Biosensing With Plasmonic Nanoaperture Tweezersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29,128–131 ] To meet this demand, nano‐aperture POTs have been combined with Raman spectroscopy. [ 132,133 ] Kerman et al experimentally demonstrated the detection and identification of single dielectric nanoparticles trapped in plasmonic nanopores. Raman tweezers comprised of gold coated plasmonic nanopores with intensely confined local fields are capable of trapping and identifying a 20 nm polystyrene nanoparticles with a single SERS peak at 785 cm −1 ( Figure a).…”
Section: Biosensing With Plasmonic Nanoaperture Tweezersmentioning
confidence: 99%
“…Reproduced with permission. [ 133 ] Copyright 2015, OSA Publishing. b) Optical transmission of 20 nm titania nanoparticle trapped in a double‐nanohole optical tweezer system shown inset.…”
Section: Biosensing With Plasmonic Nanoaperture Tweezersmentioning
confidence: 99%
“…A plasmonic nanoslit is an optically engineered elongated nanopore structure, which has been studied in depth by Chen et al [9,10,14,43,59,[75][76][77][78] As shown in Figure 4e, a nanoslit coated with Au locates at the bottom of an inverted triangular cavity, with periodic shallow grooves on both sides of the cavity to optimize the field enhancement inside the nanoslit. The nanoslit cavity works as a primary antenna to confine SPPs in the cavity, whereas the periodic grooves work as Bragg mirror nanoantennas to reflect the leakage of SPPs back into the nanoslit cavity, or are designed to collect electromagnetic energy from a wide area.…”
Section: Several Kinds Of Plasmonic Nanoporesmentioning
confidence: 99%
“…[9] As for temporal resolution, new functionalities offered by laser or plasmonics make it possible to control the translocation mechanism of molecules. The translocation time of analytes can be tuned from microseconds to seconds, [10][11][12][13][14] which dramatically improves the temporal resolution. In addition, the unique sensitivity and specificity of optical signals will complement the limitations of traditional electrical signals.…”
mentioning
confidence: 99%
“…They measured two color codes and presented the ability to read single nucleotide base but with 10% identification error. Others suggested the application of plasmonic structures for unzipping method with a report of simulation results [88,89]. In their report, surface-enhanced Raman signal could separate the information of different nucleotides along DNA strand.…”
Section: Optical Detectionmentioning
confidence: 99%